Airborne Observations of CFCs Over Hebei Province, China in Spring 2016. Issue 18 (13th September 2021) - Benish, Sarah E.; Salawitch, Ross J.; Ren, Xinrong; He, Hao; Dickerson, Russell R.
Abstract: In Spring 2016, 27 whole air samples were collected from an aircraft ∼500–∼3, 500 m over Hebei Province, China and analyzed for 16 halocarbons, including chlorofluorocarbons (CFCs). Mixing ratios (median, 25th–75th percentiles) of CFC‐11 (281, 255–318 ppt), CFC‐12 (546, 473–591 ppt), CFC‐113 (79, 73–85 ppt), CFC‐114 (22, 19–25 ppt), HCFC‐22 (345, 308–432 ppt), and CCl4 (88, 75–104 ppt) were often observed to be higher than their global tropospheric background levels. The significantly elevated mixing ratios of ozone depleting substances (ODSs) combined with strong correlations with anthropogenic tracers known to have substantial use and emission in this region (HCFC‐22 and CH2 Cl2 ) suggest continuing emissions of multiple Montreal Protocol‐controlled gases at the time of measurement. We use HYSPLIT trajectory clusters and potential source contribution function methods to identify principal transport pathways of CFCs. We find the highest mixing ratios of ODSs in air originating from Inner Mongolia, Hebei, and Shandong. The strong correlations between CFC‐11 and CFC‐12 with the feedstock CCl4 suggest new production is prevalent in all three regions. We find no evidence for new production of CFC‐113, but the strong correlation of CFC‐114 with the feedstock C2 Cl4 suggests new production of CFC‐114 from the southeast of China. The findings of this study confirm high mixing ratios of ODSs over Hebei in Spring 2016 and suggest new production and use (rather than release from banks), which is in conflict with the Montreal Protocol agreement that bans the production of CFCs. Plain Language Summary: Chlorofluorocarbons (CFCs) were banned by the Montreal Protocol since these compounds lead to stratospheric ozone depletion, resulting in a rapid decline in emissions starting in the 1980s. Recent studies show that emissions of CFC‐11 have increased, and suggest a contribution from eastern Asia. In this study, we examine airborne observations (May–June 2016) of CFCs and other halogen containing compounds over a region in China previously identified with likely new production of CFC‐11. We find high mixing ratios of many compounds well above the global tropospheric background. Combined with strong correlations with other man‐made compounds still used in China, we conclude emission and possible new production of CFCs continued during Spring 2016 despite the global phaseout. The largest mixing ratios of CFCs are traced to Inner Mongolia, Shandong, and Hebei. Based upon correlations of CFCs with compounds used in their manufacture, we identify regions of new CFC production. We find evidence of new production of CFC‐11 and CFC‐12 throughout eastern China, while new production of CFC‐114 is limited to flow from the southeast. No evidence is found to suggest new production of CFC‐113. Our observations demonstrate new production of CFC‐11, CFC‐12, and CFC‐114 in various regions of China during Spring 2016. Key Points: Abundance of chlorofluorocarbons (CFCs) and ozone depleting substances observed throughout the boundary layer over Hebei Province, China were well above 2016 global background levels Evidence of new production of CFCs includes positive correlations with the feedstocks CCl4 and C2 Cl4 Elevated CFCs are associated with trajectories that recently passed over either Inner Mongolia, Shandong Province, or Hebei Province